1996
DOI: 10.1111/j.1095-8649.1996.tb00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Date of smolt migration depends on body‐size but not age in wild sea‐run brown trout

Abstract: Wild, one-and two-summers-old sea-trout parr in a small stream, were tagged with PIT-tags in late autumn and recaptured in a smolt trap during the following spring. One-summer-old smolts migrated later than older ones and were smaller at migration. ANCOVA indicated that migration date was negatively related to body length at tagging, but we found no significant effect of age or condition factor at tagging on this relation. The difference in timing between the age-classes was thus an effect of body size rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 25 publications
9
35
1
Order By: Relevance
“…We observed that larger individuals migrated sooner, which is a well-supported pattern in 309 the literature (Metcalfe et al 1990; Bohlin et al 1996). Because fish of larger size may have 310 higher growth rates and higher metabolic rates than their smaller counterparts (Økland et al 311 1993; Thorpe et al 1998), we would predict that larger individuals have higher levels of 312 oxidative stress.…”
Section: Discussion 282supporting
confidence: 71%
“…We observed that larger individuals migrated sooner, which is a well-supported pattern in 309 the literature (Metcalfe et al 1990; Bohlin et al 1996). Because fish of larger size may have 310 higher growth rates and higher metabolic rates than their smaller counterparts (Økland et al 311 1993; Thorpe et al 1998), we would predict that larger individuals have higher levels of 312 oxidative stress.…”
Section: Discussion 282supporting
confidence: 71%
“…We observed a greater length at tagging of age-1 and age-2 migrants compared with similarly aged nonmigrants, which supports the second hypothesis. This observation may also suggest a critical size threshold must be reached before migration (Bohlin et al 1996). However, most tagged individuals exceeded a critical size without migrating, and back-calculated length from otoliths was similar between migrants and nonmigrants.…”
Section: Discussionmentioning
confidence: 73%
“…At this point, the fry start to feed and establish territories (Elliott 1994; Héland 1999). In Norumsån, juveniles normally stay in the stream for one or two summers before migrating to the sea in the following spring, typically at a size of 70–160 mm (Bohlin et al 1993, 1996). However, depending on body condition in the previous year, up to half of the 1-year-old males, and a lower proportion of females, stay in the stream as resident adults (Dellefors and Faremo 1988; Bohlin et al 1994, Pettersson 2002).…”
Section: Methodsmentioning
confidence: 99%